1975
DOI: 10.1007/bf01911641
|View full text |Cite
|
Sign up to set email alerts
|

The thermal study of pseudohomogeneous ion-exchange membranes

Abstract: Derivatograph was used to investigate pseudohomogeneous ion-exchange membranes. Two membrane types were examined: a) a membrane obtained from polyethylene film modified with the copolymer of styrene and DVB; and b) membrane AMF C-311 obtained on a film of fluorinated polymeric material.Although differential thermal analysis (DTA) has been used in the investigation of polymers only recently, a large number of papers concerning different problems in this field have already appeared. Only a few of these papers, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Thermal analysis of some arylsulphanylamines containing benzene and naphthalene rings, resp., indicated that the compounds containing benzene rings have higher thermal stability [125]. Polish researchers report investigations of pseudo-homogeneous two-phase ion exchange membranes [126].…”
Section: Fundamental and Applied Research Resultsmentioning
confidence: 99%
“…Thermal analysis of some arylsulphanylamines containing benzene and naphthalene rings, resp., indicated that the compounds containing benzene rings have higher thermal stability [125]. Polish researchers report investigations of pseudo-homogeneous two-phase ion exchange membranes [126].…”
Section: Fundamental and Applied Research Resultsmentioning
confidence: 99%